A construção coletiva dos espaços livres públicos : o arquiteto e os procedimentos participativos : recentes experiências em Vitória (ES) - Aliprandi, Danielly Cozer (2011)
During the city development, there are three main agents. The State, the technicians from different fields and societies. A diversity of groups makes part of that society, from which we can highlight, based on the participation in the political decisions,